Evaluación de un tratamiento fotocatalítico en la disminución de fenol para la empresa Proicsa Ingenieria S.A.S. (2019)
The titanium dioxide (TiO2) catalyst was obtained by means of a hydrolysis reaction, using as reagent titanium tetrabutoxide (Ti (OCH2CH2CH3) 4), in order to obtain a saturated suspension of the semiconductor, this synthesis process was carried out carried out under shaking speeds of 400 and 1200 rpm with pH values of 2 and 4, in this way the 1,2,3 and 4 catalysts were obtained by Dip-coating technique, with which the process was carried out of degradation for phenol concentrations of 10, 5, 3 and 0.5ppm, in addition to the waste generated by Proicsa. The degradation of the phenol solutions and the waste of the company was carried out in a PVC photoreactor with a reaction time of 5 hours, with agitation supplied by bubbling. In order to verify the decrease in phenol concentration and determine the reaction rate, the phenol determination analyzes were carried out by means of the technique "Chloroform extraction and spectrophotometric determination" at different time intervals, additionally as a parameter of verification of the degradation, the COD was determined at the beginning and end of the photocatalytic process by means of the technique of "closed reflux and volumetry".